Preparation method and application of hollow prismatic cobalt iron oxide heterogeneous Fenton-like catalyst

By preparing hollow prism-shaped cobalt iron oxide heterogeneous Fenton catalyst, the problem of large catalyst do not thoroughly degraded in the prior art is solved, and the effect of efficient degradation of difficult-to-degrade organic pollutants is achieved, and good stability and cycling performance are demonstrated.

CN115920899BActive Publication Date: 2025-04-25NANCHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310011143.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-05
Publication Date
2025-04-25
Estimated Expiration
2043-01-05

AI Technical Summary

Technical Problem

In the prior art, when catalyzing the degradation of permonosulfate (PMS) and difficult to degrade organic pollutants, the catalyst amount is large and the degradation is not thorough, and most reactions only occur on the sample surface, lacking methods to effectively improve catalytic performance.

Method used

The bimetallic composite oxide was successfully prepared by self-sacrificing template method and calcination using hollow prismatic cobalt iron oxide heterogeneous Fenton catalyst (CoFeO-Prism), with a higher specific surface area and more catalytically active sites.

Benefits of technology

It significantly improves the oxidation efficiency of PMS, can efficiently degrade difficult-to-degrade organic pollutants, such as RhB and TC-HCl, and has good water stability, thermal stability and recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115920899B_ABST
    Figure CN115920899B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a hollow prismatic cobalt iron oxide heterogeneous Fenton-like catalyst, wherein the cobalt iron oxide heterogeneous Fenton-like catalyst is CoFeO-Prism, which is a composite oxide of Co3O4 and Fe3O4, and the morphology of the CoFeO-Prism is a micrometer-scale hollow prismatic structure. The preparation method includes: using polyvinyl pyrrolidone and cobalt acetate tetrahydrate as raw materials, using ethanol as solvent, and heating to obtain a Co-Prism precursor; the Co-Prism precursor dispersed in anhydrous ethanol and K3[Fe(CN)6] dissolved in deionized water are stirred and mixed at room temperature to generate Co-Fe PBA-Prism; Co-Fe PBA-Prism is calcined to 200-300°C for reaction, and the heating is stopped and the reactor is opened and cooled to room temperature to obtain CoFeO-Prism. The hollow material of the present invention has a higher specific surface area, has more exposed catalytic active sites, and effectively improves the catalytic efficiency of the catalyst. The present invention can significantly improve the oxidation efficiency of PMS, and exhibits excellent performance in activating PMS to degrade organic pollutants, especially dyes, antibiotics and other difficult-to-degrade organic pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of organic wastewater treatment, and in particular to a preparation method and application of a hollow prism-shaped cobalt-iron oxide heterogeneous Fenton-like catalyst. The bimetallic oxide material can be used to catalyze the degradation of refractory organic pollutants in water by peroxymonosulfate (PMS). Background Art

[0002] Refractory organic pollutants such as dyes and antibiotics have become priority toxic pollutants due to their stable structure, high toxicity, and difficulty in treatment. In recent years, many scholars have used catalytic degradation, activated carbon adsorption and other methods to degrade refractory organic pollutants, but most methods are only suitable for treating high-concentration pollutants and have the disadvantages of long treatment time, incomplete treatment, high cost, and easy to cause secondary pollution, which limits their large-scale application.

[0003] Nowadays, the technology of using transition metal oxide nanomaterials to treat organic pollutants is rapidly emerging, among which cobalt iron oxide is gradually favored by researchers as an environmentally friendly material. Studies have shown that cobalt iron elements themselves are good catalytic sites and have a certain catalytic effect on sulfate. Using them to catalytically oxidize PMS can achieve the purpose of degrading difficult-to-degrade pollutants. At present, researchers have synthesized bimetallic oxides to catalyze PMS to degrade difficult-to-degrade pollutants, but most studies require a large amount of catalyst and have the disadvantage of incomplete degradation. Studies have shown that most catalytic oxidations only occur on the surface of the sample. Compared with solid materials, hollow materials have a higher specific surface area and more exposed catalytic active sites. Therefore, exploring the preparation method of hollow cobalt iron oxide with adjustable morphology is of great significance to improving catalytic performance. Summary of the invention

[0004] In view of the deficiencies and difficulties in the prior art, the present invention aims to provide a method for preparing a hollow prismatic cobalt iron oxide heterogeneous Fenton-like catalyst and its application. The bimetallic oxide material can be used to catalyze the degradation of refractory organic pollutants in water by peroxymonosulfate (PMS).

[0005] The present invention is achieved through the following technical solutions:

[0006] On the one hand, the present invention discloses a hollow prismatic cobalt iron oxide heterogeneous Fenton-like catalyst. The cobalt iron oxide heterogeneous Fenton-like catalyst is CoFeO-Prism. CoFeO-Prism is a composite oxide of Co3O4 and Fe3O4. The morphology of CoFeO-Prism is a micrometer-scale hollow prismatic structure.

[0007] The present invention also provides a method for preparing a hollow prism-shaped cobalt iron oxide heterogeneous Fenton-like catalyst, the preparation method comprising the following steps:

[0008] 1. Preparation of Co-Prism precursor, including:

[0009] (1) dissolving polyvinyl pyrrolidone and cobalt acetate tetrahydrate in a solvent ethanol to form a transparent solution at room temperature, wherein the mass ratio of polyvinyl pyrrolidone, cobalt acetate tetrahydrate and ethanol is 1:0.4-1.2:100-300;

[0010] (2) heating the transparent solution to 80-90°C under reflux conditions to react for 1-3 hours;

[0011] (3) washing and centrifuging the reaction solution at least 10 times to obtain a centrifugal product;

[0012] (4) Dry the centrifuged product in an oven at 50-70 °C for 8-16 hours to obtain a Co-Prism precursor.

[0013] 2. Preparation of Co-Fe PBA-Prism, specifically:

[0014] (1) ultrasonically dispersing the Co-Prism precursor into anhydrous ethanol to obtain emulsion A;

[0015] (2) Dissolve K3[Fe(CN)6] in deionized water to obtain a transparent yellow solution, which is referred to as solution B;

[0016] (3) stirring and mixing emulsion A and solution B at room temperature for 0.5 to 2 hours, wherein the mass ratio of the Co-Prism precursor to K3[Fe(CN)6] is 1:1 to 3;

[0017] (4) The reaction product was separated by centrifugation, washed several times with deionized water and anhydrous ethanol, and dried in an oven at 60 °C overnight to obtain Co-Fe PBA-Prism.

[0018] 3. Preparation of CoFeO-Prism, specifically: heating Co-Fe PBA-Prism to 200-300°C (preferably 250°C) for calcination reaction for 1-2 hours (preferably 1.5 hours), stopping heating, opening the reactor and cooling to room temperature, taking out the reaction product from the reactor and grinding it to obtain powdered CoFeO-Prism.

[0019] The present invention also provides the use of the hollow prism-shaped cobalt iron oxide heterogeneous Fenton-like catalyst prepared by the above method, wherein CoFeO-Prism is used as a catalyst to activate peroxymonosulfate PMS, and is used to degrade refractory organic pollutants in organic wastewater.

[0020] Furthermore, the mass ratio of the dosage of CoFeO-Prism to PMS is 1:0.15-6; the initial pH of the reaction is adjusted to 4-10; and the reaction temperature is 15-35°C.

[0021] Furthermore, when degrading RhB in organic wastewater, the mass ratio of the dosage of CoFeO-Prism to PMS is 1:0.5; and the initial pH of the reaction is adjusted to 7-9.

[0022] Furthermore, when TC-HCl is used to degrade organic wastewater, the mass ratio of the added amount of CoFeO-Prism to that of PMS is 1:1; and the initial pH of the reaction is adjusted to 8-10.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) Compared with solid materials, the hollow materials of the present invention have a higher specific surface area and more exposed catalytic active sites, which makes the active sites contact with pollutants in the solution more frequently, thus helping to improve the catalytic efficiency of the catalyst.

[0025] (2) The present invention successfully prepared various PBA derivatives with regular morphology and uniform size through a simple self-sacrificial template method and calcination. The bimetallic composite oxide composed of Co3O4 and Fe3O4 is micrometer-sized and presents a hollow morphology.

[0026] (3) The CoFeO-Prism catalyst of the present invention can significantly improve the oxidation efficiency of PMS, and exhibits excellent performance in activating peroxymonosulfate (PMS) to degrade organic pollutants, especially RhB, TC-HCl and other difficult-to-degrade organic pollutants.

[0027] (4) The CoFeO-Prism of the present invention has good water stability and thermal stability, as well as recyclability at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The CoFeO-Prism XRD pattern in Example 2 is compared with the Fe3O4 and CoFe2O4 PDF cards;

[0029] Figure 2 SEM images of CoFeO-Prism (c, d) in Example 2;

[0030] Figure 3 TEM images of CoFeO-Prism (a, b) in Example 2;

[0031] Figure 4 This is the full spectrum scan of CoFeO-Prism XPS in Example 2;

[0032] Figure 5 This is the CoFeO-Prism XPS Co2p narrow spectrum high-resolution scan in Example 2;

[0033] Figure 6 It is the CoFeO-Prism XPS Fe2p narrow spectrum high resolution scan in Example 2;

[0034] Figure 7 The linear fit of the RhB standard curve in Example 3;

[0035] Figure 8 This is a comparison chart of the adsorption and degradation of PMS alone and CoFeO-Prism in Example 3;

[0036] Fig. 9 This is a comparison chart of the degradation of CoFeO-Prism and CoFeO-Cube in Example 3;

[0037] Fig.10 The experimental curve (a) and kinetic fitting curve (b) of CoFeO-Prism dosage variation in Example 3;

[0038] Fig.11 The experimental curve (a) and kinetic fitting curve (b) of PMS dosage variation in Example 3;

[0039] Fig.12 The temperature change experimental curve (a) and the kinetic fitting curve (b) in Example 3;

[0040] Fig.13 The initial pH change experimental curve (a) and the kinetic fitting curve (b) in Example 3;

[0041] Fig.14 The cycle test curve 14 in Example 3

[0042] Fig.15 The catalyst air atmosphere TGA curve 1 in Example 3

[0043] Fig.16 The free radical quenching experimental curve (a) and the kinetic fitting curve (b) in Example 3;

[0044] Fig.17 Fitting the TC-HCl standard curve in Example 4;

[0045] Fig.18 This is the experimental curve of PMS single addition, CoFeO adsorption, and TC-HCl degradation in Example 4;

[0046] Fig.19Comparison of the catalytic effects of CoFeO-Prism and CoFeO-Cube in Example 4;

[0047] Fig. 20 The experimental curve (a) and kinetic fitting curve (b) of CoFeO-Prism dosage variation in Example 4;

[0048] Fig.21 The experimental curve (a) and kinetic fitting curve (b) of PMS dosage variation in Example 4;

[0049] Fig. 22 The temperature change experimental curve (a) and the kinetic fitting curve (b) in Example 4;

[0050] Fig.23 The initial pH change experimental curve (a) and the kinetic fitting curve (b) in Example 4;

[0051] Fig.24 This is the catalyst circulation test curve in Example 4;

[0052] Fig.25 The free radical quenching experimental curve (a) and the kinetic fitting curve (b) in Example 4. DETAILED DESCRIPTION

[0053] The present invention will be further described below in conjunction with the accompanying drawings.

[0054] Example 1. Preparation of CoFeO-Prism Catalyst

[0055] Step 1. Preparation of Co-Prism Precursor

[0056] 1. Weigh 1.0 g polyvinyl pyrrolidone (PVP, K30) and 0.64 g cobalt acetate tetrahydrate, dissolve them in 200 mL ethanol at room temperature to form a transparent solution, and transfer it to a 500 mL round-bottom flask.

[0057] 2. Heat the solution in 1 to 85°C under reflux and react for 2 hours.

[0058] 3. Wash and centrifuge the solution at least 10 times to obtain a centrifugal product.

[0059] 3. Dry the centrifuged product in an oven at 60°C overnight to obtain the Co-Prism precursor.

[0060] Step 2, Preparation of Co-Fe PBA-Prism

[0061] 1. Weigh 0.02 g of Co-Prism precursor and add it to 20 mL of anhydrous ethanol. Ultrasonic disperse it into the ethanol as emulsion A.

[0062] 2. Weigh 0.02 g of K3[Fe(CN)6] and dissolve it in 20 mL of deionized water to obtain a transparent yellow solution as solution B.

[0063] 3. Emulsion A and solution B were mixed together and stirred at room temperature, and reacted at room temperature for 1 hour.

[0064] 4. The reaction product was separated by centrifugation, washed with deionized water and anhydrous ethanol for several times, and dried in an oven at 60 °C overnight to obtain Co-Fe PBA-Prism.

[0065] Step 3, CoFeO-Prism preparation

[0066] 1. Weigh a certain amount of Co-Fe PBA-Prism and add it into the crucible.

[0067] 2. Place the crucible in a muffle furnace and heat to 250 °C for 1.5 h.

[0068] 3. Open the muffle furnace to cool down. After the furnace temperature drops, take out the crucible and let it cool naturally. After grinding, CoFeO-Prism is obtained.

[0069] Example 2: Structural Characterization and Analysis of CoFeO-Prism

[0070] 1. XRD analysis

[0071] In order to determine the crystal structure characteristics and phase information of the synthesized material, the synthesized CoFeO-Prism material was tested by XRD. The results are as follows Figure 1 As shown. Figure 1 It can be seen that the CoFeO-Prism XRD pattern has four diffraction peaks at 2θ=36.82°, 44.76°, 59.30° and 65.19°, which correspond to the characteristic diffraction peaks of the (311), (400), (511) and (440) crystal planes of the ferroferric oxide structure in the material Fe3O4 standard PDF card 26-1136.

[0072] The characteristic diffraction peaks of the (311), (400), (511) and (440) crystal planes of the Co3O4 structure in standard PDF#42-1467 are basically consistent with those in PDF#26-1136. The characteristic peaks of iron-cobalt oxide are basically overlapping and basically consistent with the overall XRD image of the sample. In addition, the image of the cobalt-iron spinel in reference PDF#22-1086 shows that the main characteristic peaks have a certain offset compared with the image of ferroferric oxide / cobalt. As far as the XRD image is concerned, the sample should be a mixed oxide of Fe3O4 and Co3O4.

[0073] 2. SEM morphology and structural analysis

[0074] Figure 2 Figures c and d are SEM images of CoFeO-Prism. It can be seen that after calcination at 250 °C in air, the basic structure of PBAs remains intact, and the hollow prism morphology is successfully inherited to the oxide derivatives. The surface of the oxide derivative becomes rough and no longer smooth compared to the Prussian blue analogue, but the overall morphology of the material remains intact, indicating that in this study, the prismatic morphology of Co-Prism was successfully inherited to the oxide derivatives through low-temperature calcination.

[0075] Comparison of the two SEM images shows that the basic morphology of PBA can be perfectly preserved in the derivatives through calcination in a stable oxygen atmosphere. The PBA derivatives can inherit the hollow prism structure of the precursor PBA relatively well, which also shows that this study has successfully prepared various PBA derivatives with regular morphology and uniform size through a simple self-sacrificial template method and calcination.

[0076] 3. TEM morphology and structural analysis

[0077] (1) CoFeO-Prism TEM image

[0078] Figure 3 a, b are TEM images of CoFeO-Prism. Through the TEM images, we can clearly see that CoFeO-Prism retains the hollow morphology of Co-Fe PBA-Prism, which shows that this study successfully inherited the hollow morphology in PBAs to the oxide derivatives through the self-sacrificial template method calcination.

[0079] From the electron microscope image, the hollow morphology appears from the PBA stage and is successfully inherited to subsequent derivatives. The solid cube and its derivatives do not have similar morphology. From the structural characterization, CoFeO is still a micrometer-scale compound and presents a hollow morphology, but no obvious holes are seen on the outer surface of CoFeO-Prism.

[0080] 4. CoFeO-Prism XPS analysis

[0081] XPS analysis was performed on the hollow prism PBA derivative product, the element valence state on the sample surface was detected, and a qualitative analysis was performed to determine the elemental composition on the sample surface and the valence state composition of the corresponding elements. The chemical composition of the sample was determined in combination with the bulk phase characterization information of XRD.

[0082] (1) Full spectrum scan

[0083] The XPS full spectrum scan of CoFeO-Prism is shown in Figure 4As shown, unlike Co-Fe PBA-Prism and Co7Fe3@C-Prism, the relative peak intensity of the O1s peak has been significantly improved, while the N1s peak intensity has been greatly reduced, which is consistent with the fact that CoFeO-Prism itself is a product calcined in an air atmosphere. Qualitatively, the elemental composition is consistent with the XRD phase analysis.

[0084] (2) Co2p narrow spectrum high-resolution scanning image

[0085] The Co2p narrow spectrum high-resolution scan fitting diagram of CoFeO-Prism is shown in Figure 5 As shown in the figure, it can be clearly seen that there are two sets of double-peak composite peaks and two satellite peaks, among which 780.3 eV is trivalent cobalt (2p 3 / 2 ), 782.1 eV divalent cobalt (2p 3 / 2 ), 795.6 eV for trivalent cobalt (2p 1 / 2 ), 797.4 eV divalent cobalt (2p 1 / 2 ), which is consistent with the XPS peak distribution of Co3O4, and the XRD spectrum also shows a composite oxide of Co3O4 and Fe3O4 of CoFe.

[0086] (3) Fe2p narrow spectrum high resolution scanning image

[0087] The Fe2p narrow spectrum high-resolution scanning fitting diagram of CoFeO-Prism is shown in Figure 6 As shown in the figure, it can be seen that there are two groups of double peaks and satellite peaks. The peak at 710.5 eV belongs to the divalent iron element (2p 3 / 2 ), the peak at 713 eV belongs to the trivalent iron element (2p 3 / 2 ), the satellite peak at 719 eV is the divalent iron satellite peak, and the peak at 724.1 eV belongs to the divalent iron element (2p 1 / 2 ), the peak at 726.1 eV belongs to the trivalent iron element (2p 1 / 2 ). From the data analysis, it can be seen that there are both divalent iron and trivalent iron on the surface of CoFeO-Prism. The XRD bulk structure information is Fe3O4. It can be considered that it is consistent with the XRD characterization results. CoFeO-Prism is a composite oxide of Fe3O4 and Co3O4.

[0088] Judging from the XPS spectrum data, the characterization information of XRD is consistent. It can be basically considered that the synthesized material is consistent with the XRD spectrum identification, which is a mixed oxide of Co3O4 and Fe3O4.

[0089] Example 3: CoFeO-Prism activated PMS to degrade Rhodamine B

[0090] 1. Feasibility analysis

[0091] In the present invention, the concentration of rhodamine B (RhB) is measured by UV-visible spectrophotometry. A certain amount of RhB powder is weighed and dissolved in deionized water to prepare RhB aqueous solutions with concentrations of 1, 5, 10, 25 and 50 ppm, which are recorded as RhB1 to RhB5. According to the literature and the absorbance value of the full wavelength scan of 200 to 800 nm by UV-visible spectrophotometer, it is determined that the maximum absorption peak of RhB used in this study appears at 554 nm.

[0092] The absorbances A1~A5 of the solutions RhB1~RhB5 were measured at 554 nm in a UV-visible spectrophotometer, and a standard curve was drawn with the absorbance A as the Y-axis ordinate and the RhB concentration as the X-axis abscissa. Figure 7 As shown, the corresponding linear regression equation is Y=0.032X-0.0086, and the correlation coefficient R 2 =0.99999, which indicates that the absorbance of RhB at 554 nm has a strong linear correlation with the concentration of RhB aqueous solution, indicating that UV-visible spectrophotometry can accurately measure RhB aqueous solution in the concentration range of 1~50 ppm, and it is feasible to use UV-visible spectrophotometry to measure the degradation effect of RhB.

[0093] The absorbance of the RhB aqueous solution with a concentration of 25 ppm was measured five times, and the obtained absorbances were 0.789, 0.789, 0.790, 0.789, and 0.790, respectively. The precision of the experiment was evaluated by the standard deviation (SD) and the relative standard deviation (RSD).

[0094]

[0095]

[0096] According to the calculation, SD = 0.000547, RSD = 0.000694. For the same concentration, the smaller the SD and RSD values, the higher the measurement precision, so the UV-visible spectrophotometry method has good precision in measuring the same sample of RhB.

[0097] 200 mL of 25 ppm RhB solution was measured and poured into a 250 mL brown stoppered conical flask for reaction. It was left for 1 h and samples were taken at 15, 30, 45, and 60 min. The measured absorbance was 0.789, 0.789, 0.790, and 0.789. According to the formula, SD=0.0005 and RSD=0.000633 were calculated, indicating that the UV-Vis spectrophotometry method had good stability and precision in measuring RhB within the duration of the experiment.

[0098] In summary, the use of UV-visible spectrophotometer to measure the absorbance of RhB can determine the subtle changes in its concentration and the real-time degradation in real time. The pre-experimental reaction UV-visible spectrophotometry is stable and has good precision. In addition, the operation is simple and can be analyzed in real time. It has great advantages in measuring the activated PMS catalytic reaction, so this method was selected for the subsequent RhB measurement.

[0099] 2. Catalytic degradation experiment

[0100] In order to explore whether CoFeO catalyst can adsorb RhB, activate PMS and the degradation effect of PMS itself, a comparative experiment of CoFeO was carried out. Experiments were conducted by adding CoFeO alone, PMS alone and CoFeO and PMS at the same time. The experimental degradation curves are shown in Figure 2. Figure 8 .

[0101] like Figure 8 It can be seen that after adding CoFeO alone, the absorbance did not change significantly, which indicates that there was no obvious adsorption between CoFeO and RhB. After adding PMS alone, the absorbance of the solution decreased, which indicates that PMS has a certain degradation effect on RhB, and about 5% of RhB is degraded within 30 minutes (2.5 ppm). When PMS and CoFeO are added at the same time, it can be seen that the absorbance of RhB has decreased significantly, indicating that RhB is significantly degraded, and the degradation rate is about 99% at 30 minutes. This shows that CoFeO can effectively activate PMS, thereby efficiently catalyzing the PMS-like Fenton reaction to degrade RhB.

[0102] 3. Comparative experiment with corresponding solid catalyst

[0103] 0.1 g / L CoFeO-Prism and CoFeO-Cube were added to the reaction, and the reaction curves were as follows: Fig. 9 shown.

[0104] It can be clearly seen from the reaction curve that the catalytic activity of CoFeO-Prism is higher than that of CoFeO-Cube. It is speculated that the hollow morphology increases the specific surface area of ​​the catalyst, exposing more active sites, making the active sites contact with pollutants in the solution more frequently, which helps to improve the catalytic efficiency of the catalyst.

[0105] 4. Effect of catalyst dosage on degradation effect

[0106] In order to explore the effect of CoFeO dosage on the degradation effect, the CoFeO dosage was changed for comparative experiments. The degradation curve and kinetic fitting curve are shown in Fig.10 And as shown in Table 1.

[0107] Table 1 Kinetic fitting curve parameters

[0108]

[0109] like Fig.10 It can be seen that at lower catalyst concentrations, the reaction rate is slow, and only about 70% RhB can be degraded in 30 min. As the catalyst concentration increases to 0.1 g / L, the degradation rate reaches 99% in 30 min. After further increasing the catalyst concentration to 0.15 g / L, no significant increase in the degradation rate is observed.

[0110] As shown in Table 1, the reaction rate constants were 0.04119, 0.10438, and 0.12104 min at 0.05 g / L, 0.1 g / L, and 0.15 g / L catalyst dosages, respectively. -1 . It can be seen that the amount of catalyst added has a great influence on the reaction rate constant. It is speculated that the low concentration of catalyst added makes the concentration of catalyst in the solution low, which reduces the probability of effective collision and fails to fully activate PMS to generate free radicals to oxidize pollutants. When the catalyst concentration increases to a certain level, due to the limitation of the amount of PMS added, the excess catalyst has no more PMS to activate and cannot participate in the reaction, which makes the reaction rate increase not obvious. From the perspective of the reaction rate constant, there is little difference between 0.15 g / L and 0.1 g / L, which is obviously close to the activation limit of the catalyst at this PMS concentration.

[0111] 5. Effect of PMS dosage on degradation effect

[0112] In order to explore the effect of PMS dosage on the degradation effect, the PMS dosage was changed for comparative experiments. The degradation curve and kinetic fitting curve are shown in Fig.11 and Table 2.

[0113] Table 2 Kinetic fitting curve parameters

[0114]

[0115] like Fig.11 It can be seen that at a PMS dosage of 0.05 g / L, the degradation reaction rate is slow, and only about 80% RhB can be degraded in 30 min. As the catalyst concentration increases to 0.05 g / L, the degradation rate reaches 99% in 30 min. When the catalyst concentration is further increased to 0.10 g / L, the degradation rate decreases instead of increasing, and the rate constant changes from 0.09327 min -1 Reduced to 0.06799min -1 , the degradation rate at 30 min was slightly reduced. It is speculated that in this system, the PMS concentration of 0.10 g / L was too high for the organic matter to be degraded, which triggered the scavenging effect. The specific formula is as follows:

[0116]

[0117] Excessive addition of PMS will remove free radicals, resulting in a slower reaction rate and lower reaction efficiency.

[0118] 6. Effect of different temperatures on catalytic effect

[0119] Since the ambient water temperature has a great influence on the liquid phase catalytic degradation rate, in order to explore the effect of reaction temperature on the catalytic effect, comparative experiments at different temperatures were conducted. The 288 K temperature is the actual water temperature of the laboratory outlet water (autumn). The ambient water temperature was adjusted using a water bath heating device, and the water temperature was heated to 298 K and 308 K for the experiment. The degradation curves and kinetic fitting curves of the comparative experiment are shown in Figure 2. Fig.12 And as shown in Table 3.

[0120] Table 3 Kinetic fitting curve parameters

[0121]

[0122] like Fig.12 It can be clearly observed that at 288 K, the degradation reaction rate is much lower than that at 298 K and 308 K, and the rate constant changes from 0.09327 and 0.10824 at 298 K and 308 K to 0.02776 min -1 , which is reduced by an order of magnitude. It can be seen that low temperature has a great influence on the reaction, and heating has a certain improvement on the reaction rate. It is speculated that it is affected by the thermal activation effect of PMS itself. Persulfate will spontaneously activate to produce persulfate radicals when it is heated. The thermal activation mechanism is as follows:

[0123]

[0124] In addition, heating causes the number of activated molecules to increase, and the effective collisions in the solution increase, which makes the reaction rate faster. However, in a low-temperature environment, the number of activated molecules is relatively small, and there are not enough effective collisions in the solution, which makes the reaction rate lower.

[0125] 7. Effect of different initial pH on catalytic effect

[0126] Generally speaking, the pH of the solution plays an important role in the Fenton-like degradation of pollutants. In order to obtain the effect of the initial pH value of the system on the catalyst activation of PMS to degrade RhB, this study selected integer values ​​of pH 4 to 10 for the initial pH value comparison experiment to explore the effect of the initial pH value on the catalytic effect. In this experiment, we used 0.1 mol / L NaOH solution and 0.1 mol / L HCl solution to adjust the initial pH value of the RhB solution, and compared the degradation curves of the experiment and the kinetic fitting curves. Fig.13 And as shown in Table 4.

[0127] Table 4 Kinetic fitting curve parameters

[0128]

[0129] like Fig.13 It can be seen that in the range of pH 4-10, CoFeO can achieve a degradation rate of more than 85%, and can effectively activate PMS to degrade RhB; in a neutral to weakly alkaline environment of pH 7-9, it can achieve a degradation rate of more than 95%. The reaction rate constant also shows that in a neutral and weakly alkaline environment, CoFeO has the best effect in activating PMS to degrade RhB. It can be considered that in a wide pH range, CoFeO can catalyze PMS to degrade RhB, and under neutral and weakly alkaline conditions, the degradation effect is better and the degradation speed is faster.

[0130] 8. Catalyst stability analysis

[0131] In addition to good catalytic performance, the catalyst's recycling performance is also an indispensable feature. In order to explore the reuse effect of the catalyst, the entire experimental system was kept unchanged for repeated cycle experiments. Due to the impact of the epidemic, only four cycles of research data were collected in this study, and more cycles will be carried out in subsequent studies. CoFeO was recovered and added after filtration, washing, centrifugation and drying. The four-cycle experimental data are as follows Fig.14 shown.

[0132] The data results show that under the same experimental conditions, the catalyst repeatedly removed the configured RhB dye wastewater in four cycles, and the catalytic activity of the catalyst had almost no obvious change within 30 min. The RhB degradation efficiency could still reach 96.4% in the fourth cycle, which shows that the prepared CoFeO has good stability and recyclability at room temperature.

[0133] ICP testing also showed that water stability was enhanced. Under the same reaction conditions, 7.02 mg / L of cobalt ions were leached out of the PBAs reaction water after the reaction, while only 0.41 mg / L of cobalt ions were leached out of Co7Fe3@C, which was lower than the emission standard of 1 mg / L.

[0134] In order to explore the thermal stability of the catalyst, the catalyst samples were sent to test the air atmosphere TGA curve. The specific data are as follows: Fig.15As shown. CoFeO-Prism is heated in air and its mass is slowly lost. According to the literature, the mass loss before 200 °C is mainly due to the loss of physically adsorbed water. Considering that Co3O4 and Fe3O4 are both very stable oxides within 800 °C, the subsequent weight loss may be due to the slow oxidation of the remaining organic matter during calcination at 250 °C. It can be considered that the catalyst has good thermal stability in the daily use temperature range, which is greatly enhanced compared with Co-Fe PBA-Prism.

[0135] 9. Possible mechanism of RhB degradation catalyzed by CoFeO-Prism

[0136] (1) Degradation of RhB free radical quenching experiment

[0137] In order to analyze the mechanism of CoFeO-Prism degradation of RhB, a free radical quenching experiment was conducted on CoFeO-Prism degradation of RhB to explore the common free radical types that play a role in the reaction process. and , tert-butyl alcohol (TBA) with a concentration of 1:1000 of PMS was used for quenching , 50 mM p-benzoquinone (BQ) was used for quenching , quenched with 10 mM furfuryl alcohol (FAA) , data such as Fig.16 and Table 5.

[0138] Table 5 Kinetic fitting curve parameters

[0139]

[0140] The data results show that when MeOH and FAA are added, the reaction rate is greatly reduced, and the K a From 0.01041 min without quenching -1 becomes 0.01041 min -1 (MeOH) and 0.00471 min -1 (FAA), decreased by one order of magnitude and two orders of magnitude respectively. After joining, Down to 0.05 min -1 The effect of BQ is similar to that of TBA, which indicates that in this reaction, This is similar to the view in some literature that singlet oxygen can also play a major role in heterogeneous persulfate advanced oxidation systems.

[0141] The reaction will also produce , as well as , but they are compared Not decisive.

[0142] (2) Mechanism analysis

[0143] Through the free radical quenching experiment, the dominant reaction species is as well as After the activation of persulfate, the transition metal ions themselves are also transformed. Combined with the literature, the mechanism of CoFeO catalytic activation of PMS is speculated:

[0144] Cycle of Co and Fe elements:

[0145]

[0146]

[0147] After PMS is activated, various free radicals and oxidative substances are generated:

[0148]

[0149]

[0150]

[0151]

[0152]

[0153]

[0154]

[0155]

[0156]

[0157] Free radicals and oxidized substances oxidize organic matter:

[0158] .

[0159] Example 4: Degradation of tetracycline hydrochloride by activation of PMS with CoFeO-Prism

[0160] Tetracycline antibiotics are a relatively common type of antibiotics. In this study, the most commonly used and representative tetracycline hydrochloride (TC-HCl) was selected as a representative of antibiotic wastewater for degradation experiments.

[0161] 1. Feasibility analysis

[0162] In this study, the concentration of TC-HCl was measured by UV-visible spectrophotometry. A certain amount of TC-HCl powder was weighed and dissolved in deionized water. The TC-HCl aqueous solutions with concentrations of 1, 5, 10, 25 and 50 ppm were prepared and recorded as TC1~TC5. According to the literature and the absorbance values ​​of the full wavelength scan of 200~800 nm by UV-visible spectrophotometer, it was determined that the TC-HCl used in this study had a maximum absorption peak at 360 nm.

[0163] Measure the absorbance A1~A5 of solution TC1~TC5 at 360 nm in a UV-visible spectrophotometer, and draw a standard curve with absorbance A as the Y-axis ordinate and TC-HCl concentration as the X-axis abscissa. Fig.17 As shown, the corresponding linear regression equation is Y=0.0323X, and the correlation coefficient R 2 =0.99991, which indicates that the absorbance of TC-HCl at 360 nm has a strong linear correlation with the concentration of TC-HCl aqueous solution, which shows that UV-visible spectrophotometry can accurately measure TC-HCl aqueous solution in the concentration range of 1~50 ppm, and it is feasible to use UV-visible spectrophotometry to measure the degradation effect of TC-HCl.

[0164] The absorbance of TC-HCl aqueous solution with a concentration of 25 ppm was measured five times, and the obtained absorbances were 0.819, 0.820, 0.819, 0.818, and 0.819, respectively. The precision of the experiment was evaluated by standard deviation (SD) and relative standard deviation (RSD).

[0165]

[0166]

[0167] According to the calculation, SD = 0.000447, RSD = 0.00546. For the same concentration, the smaller the SD and RSD values, the higher the measurement precision, so the UV-Vis spectrophotometry has good precision in measuring the same sample of TC-HCl.

[0168] Measure 200 mL of 25 ppm TC-HCl solution and pour it into a 250 mL brown stoppered conical flask for reaction. Leave it for 1 hour. Sampling is performed at 15, 30, 45, and 60 min. The measured absorbance is 0.820, 0.819, 0.820, and 0.820. According to the formula, SD=0.0005 and RSD=0.00061 are calculated, indicating that the UV-Vis spectrophotometry has good stability and precision in measuring TC-HCl within the duration of the experiment.

[0169] In summary, the use of UV-visible spectrophotometer to measure the absorbance of TC-HCl can determine the subtle changes in its concentration and the real-time degradation in real time. The pre-experimental reaction UV-visible spectrophotometry is stable and has good precision. In addition, the operation is simple and can be analyzed in real time. It has great advantages in measuring the activated PMS catalytic reaction, so this method is selected for the subsequent measurement of TC-HCl.

[0170] 2. Catalytic degradation experiment

[0171] CoFeO and PMS were added separately or simultaneously into 200 mL of 50 ppm TC-HCl solution for reaction. The specific reaction curves are shown in Fig.18 shown.

[0172] like Fig.18 As shown, it can be observed that when the catalyst is added alone, the absorbance of TC-HCl does not change significantly, which indicates that the catalyst has no obvious adsorption phenomenon on TC-HCl. The addition of PMS alone has a certain degradation effect. At a reaction time of 60 min, the addition of PMS alone can degrade about 8% of TC-HCl. When CoFeO-Prism is added at a dosage of 0.1 g / L and at the same time as PMS at a dosage of 0.3 g / L, the degradation rate of TC-HCl can reach 84.5% at 50 min, which indicates that CoFeO-Prism can activate the PMS Fenton reaction and can activate PMS to effectively degrade TC-HCl.

[0173] 3. Comparative experiment with the corresponding solid catalyst effect

[0174] 0.1 g / L CoFeO-Cube and CoFeO-Prism were added to the reaction, and the reaction curves were as follows: Fig.19 shown.

[0175] It can be clearly seen from the reaction curve that the catalytic activity of CoFeO-Prism is higher than that of CoFeO-Cube. It is speculated that the hollow morphology makes the active sites contact with the solution more frequently, which helps to improve the catalytic efficiency of the catalyst.

[0176] 4. Effect of catalyst dosage on degradation effect

[0177] In order to explore the effect of CoFeO dosage on the degradation effect, the RhB concentration was kept at 50 ppm, the PMS dosage was 0.3 g / L, the ambient temperature was kept at 298 K by water bath heating, and the CoFeO dosage was changed for comparative experiments. The degradation curves and kinetic fitting curves are shown in Figure 2. Fig. 20 and Table 6.

[0178] Table 6 Kinetic fitting curve parameters

[0179]

[0180] like Fig. 20 It can be seen that at a CoFeO addition concentration of 0.05 g / L, the reaction rate is slow, and 80.68% TC-HCl can be degraded in 30 min. As the catalyst concentration increases to 0.1 g / L, the degradation rate reaches 84.52% in 30 min. After further increasing the catalyst concentration to 0.15 g / L, the degradation rate increases significantly, but the final degradation efficiency is 84.82%, and no significant improvement is observed. This indicates that under this condition, the degradation rate cannot be increased by increasing the catalyst concentration.

[0181] As shown in 20, the reaction rate constants at 0.05 g / L, 0.1 g / L, and 0.15 g / L catalyst dosages were 0.05373, 0.05476, and 0.08453 min, respectively. -1 It can be seen that increasing the amount of catalyst added has a greater impact on the reaction rate constant. It is speculated that the low concentration of catalyst added makes the concentration of the catalyst in the solution low, which reduces the probability of effective collision and fails to fully activate PMS to generate free radicals to oxidize pollutants.

[0182] 5. Effect of PMS dosage on degradation effect

[0183] In order to explore the effect of PMS dosage on the degradation effect, other experimental conditions were kept unchanged and the PMS dosage was changed for comparative experiments. The degradation curve and kinetic fitting curve are shown in Fig.21 and Table 7.

[0184] Table 7 Kinetic fitting curve parameters

[0185]

[0186] like Fig.21 It can be seen that at a PMS dosage of 0.05 g / L, the degradation reaction rate was fast in the early stage, but only about 78% TC-HCl could be degraded in 30 min. As the catalyst concentration increased to 0.15 g / L, the degradation rate reached 83% in 30 min. After further increasing the catalyst concentration to 0.3 g / L, the degradation rate did not increase significantly, and the degradation rate remained at 84.52% in 30 min. It is speculated that under the CoFeO-PMS system at room temperature, the degradation rate of about 85% is already the limit.

[0187] 6. Effect of temperature on degradation effect

[0188] Since the ambient water temperature has a great influence on the liquid phase catalytic degradation rate, in order to explore the effect of reaction temperature on the catalytic effect, 288 K is the actual water temperature of the laboratory outlet water (autumn). The ambient water temperature is adjusted by a water bath heating device and the water temperature is heated to 298 K and 308 K. The other experimental conditions are kept unchanged to conduct comparative experiments at different temperatures. The parameters, degradation curves and kinetic fitting curves of the comparative experiments are shown in Figure 2. Fig. 22 and as shown in Table 8.

[0189] Table 8 Kinetic fitting curve parameters

[0190]

[0191] like Fig. 22 It can be clearly observed that at 288 K, the degradation reaction rate is much lower than that at 298 K and 308 K. The rate constant is 0.04661 min at 298 K. -1 Reduced to 0.03252 min -1 It can be seen that low temperature has a great influence on the reaction. The K a Increased to 0.10222 min -1 , which indicates that increasing the temperature greatly improves the reaction rate and the degradation efficiency is also increased to 91.7%, which is presumably due to the thermal activation of PMS.

[0192] 7. Effect of different initial pH on catalytic effect

[0193] In order to explore the effect of different initial pH of the system on the catalytic effect, the initial pH of the system was adjusted using NaOH solution and HCl solution, and the pH was adjusted to an integer pH value of 4-10. Other reaction conditions were maintained at a PMS dosage of 0.3 g / L, a catalyst dosage of 0.1 g / L, a reaction temperature of 298 K by water bath heating, and a TC-HCl concentration of 50 ppm. Specific experimental data are as follows Fig.23 and as shown in Table 9.

[0194] Table 9 Kinetic fitting curve parameters

[0195]

[0196] like Fig.23 The data results show that in the pH range of 4~10, the CoFeO catalyst can achieve a degradation rate of more than 80% for 50 ppm TC-HCl in a 50 min reaction process, and the reaction rate gradually increases with the increase of pH. Within the range of experimental exploration, the reaction rate reaches the maximum when pH=10, K a From 0.04661 min at pH = 4 without adjustment -1becomes 0.06869 min -1 This indicates that pH has an effect on the PMS advanced oxidation system, which is similar to the summary in the literature. The reason for this phenomenon should be the alkaline activation effect of PMS.

[0197] In general, the CoFeO catalyst can activate PMS to catalyze the degradation of TC-HCl simulated wastewater under different pH conditions, and the catalytic effect is stable in a wide pH range, indicating that the CoFeO catalyst has a good pH adaptability range.

[0198] 8. Catalyst circulation experiment

[0199] In addition to good catalytic performance, the recyclability of the catalyst is also an indispensable feature of the catalyst. In order to explore the reuse effect of the catalyst, the entire experimental system was kept unchanged and repeated four cycles: the PMS dosage was maintained at 0.05 g / L, the CoFeO dosage was maintained at 0.1 g / L, the TC-HCl concentration was maintained at 50 ppm, and the system ambient temperature was maintained at 298 K by water bath heating. CoFeO was recovered and then added after filtration, washing, centrifugation and drying. Due to the impact of the epidemic, only four cycles of research data were collected in this study, and more cycles will be carried out in subsequent studies. The four-cycle experimental data are as follows: Fig.24 shown.

[0200] The data results show that under the same experimental conditions, the catalyst repeatedly removed the configured TC-HCl dye wastewater in four cycles. In the four cycles, the catalytic activity of the catalyst decreased slightly within 50 min, and the TC-HCl degradation efficiency decreased from 84.6% to 80.6%, but the amplitude was not large, indicating that the prepared CoFeO has good stability and recyclability at room temperature.

[0201] 9. Analysis of the mechanism of TC-HCl degradation catalyzed by CoFeO-Prism

[0202] (1) Degradation of TC-HCl free radical quenching experiment

[0203] In order to analyze the mechanism of CoFeO degradation of TC-HCl, a free radical quenching experiment was carried out on CoFeO degradation of TC-HCl to explore the common free radical types that play a role in the reaction process. The selection and dosage of the quencher were first communicated with Example 3. The specific experimental curve is as follows: Fig.25 And Table 10:

[0204] Table 10 Kinetic fitting curve parameters

[0205]

[0206] like Fig.25The data show that the quenching effect of FAA is very significant, which is in sharp contrast to the curves of other quenchers. After adding FAA, the reaction almost stagnated after 4 minutes, and the degradation rate remained at 20%. a Also from 0.04331 min without quenching -1 becomes 0.00217 min -1 (FAA), which means It plays a dominant role in the reaction. After adding MeOH, TBA and BQ, it also has a certain effect on the reaction, and the effect of MeOH is stronger than that of TBA, which indicates that there is also , as well as , but not as good as Great impact on the reaction.

[0207] (2) Mechanism analysis

[0208] According to the above free radical quenching experimental results, it can be inferred that the mechanism of CoFeO activation of PMS to degrade TC-HCl is similar to that of activated PMS to degrade RhB, the cycle of Co and Fe elements:

[0209]

[0210]

[0211] After PMS is activated, various free radicals and oxidative substances are generated:

[0212]

[0213]

[0214]

[0215]

[0216]

[0217]

[0218]

[0219]

[0220]

[0221] Free radicals and oxidized substances oxidize organic matter:

[0222]

[0223] The above only expresses the preferred embodiments of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications, improvements and substitutions can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.

Claims

1. A hollow prismatic cobalt iron oxide heterogeneous Fenton-like catalyst, characterized in that: The cobalt iron oxide heterogeneous Fenton-like catalyst is CoFeO-Prism, and the CoFeO-Prism is a composite oxide of Co3O4 and Fe3O4. The morphology of the CoFeO-Prism is a micrometer-scale hollow prism structure, and no obvious holes are observed on the outer surface of the CoFeO-Prism; The method comprises the following steps: S1. Preparation of Co-Prism precursor: using polyvinyl pyrrolidone and cobalt acetate tetrahydrate as raw materials and ethanol as solvent, heating reaction was performed to obtain Co-Prism precursor; S2. Preparation of Co-Fe PBA-Prism: Co-Prism precursor dispersed in anhydrous ethanol and K3[Fe(CN)6] dissolved in deionized water are stirred and mixed at room temperature to react to generate Co-Fe PBA-Prism; S3. Preparation of CoFeO-Prism: calcining the Co-Fe PBA-Prism to 200-250° C. and reacting for a period of time, then stopping heating, opening the reactor and cooling to room temperature to obtain CoFeO-Prism.

2. A method for preparing the hollow prismatic cobalt iron oxide heterogeneous Fenton-like catalyst according to claim 1, characterized in that: The method comprises the following steps: S1. Preparation of Co-Prism precursor: using polyvinyl pyrrolidone and cobalt acetate tetrahydrate as raw materials and ethanol as solvent, heating reaction was performed to obtain Co-Prism precursor; S2. Preparation of Co-Fe PBA-Prism: Co-Prism precursor dispersed in anhydrous ethanol and K3[Fe(CN)6] dissolved in deionized water are stirred and mixed at room temperature to react to generate Co-Fe PBA-Prism; S3. Preparation of CoFeO-Prism: calcining the Co-Fe PBA-Prism to 200-250° C. and reacting for a period of time, then stopping heating, opening the reactor and cooling to room temperature to obtain CoFeO-Prism.

3. The method for preparing a hollow prismatic cobalt iron oxide heterogeneous Fenton-like catalyst according to claim 2, characterized in that: The step S1 specifically includes: S1-1. At room temperature, polyvinyl pyrrolidone and cobalt acetate tetrahydrate are dissolved in an ethanol solvent to form a transparent solution, wherein the mass ratio of polyvinyl pyrrolidone, cobalt acetate tetrahydrate and ethanol is 1:0.4~1.2:100~300; S1-2. Under reflux conditions, the transparent solution is heated to 60~90°C for reaction for 1~3 hours; S1-3. The reaction solution was washed and centrifuged at least 10 times to obtain a centrifugal product; S1-4. Dry the centrifuged product in an oven at 50-70 °C for 8-16 hours to obtain a Co-Prism precursor.

4. The method for preparing a hollow prism-shaped cobalt iron oxide heterogeneous Fenton-like catalyst according to claim 2, characterized in that: The step S2 is specifically as follows: S2-1. The Co-Prism precursor is ultrasonically dispersed in anhydrous ethanol to form an emulsion A; S2-2. K3[Fe(CN)6] was dissolved in deionized water to obtain a transparent yellow solution as solution B; S2-3. The emulsion A and solution B were stirred and mixed at room temperature for 0.5 to 2 hours, wherein the mass ratio of the Co-Prism precursor to K3[Fe(CN)6] was 1:1 to 3; S2-4. The reaction product was separated by centrifugation, washed with deionized water and anhydrous ethanol for several times, and dried in an oven at 60 °C overnight to obtain Co-Fe PBA-Prism.

5. The method for preparing a hollow prism-shaped cobalt iron oxide heterogeneous Fenton-like catalyst according to claim 2, characterized in that: The step S3 is specifically as follows: placing Co-Fe PBA-Prism in a reactor, heating it to 250°C, calcining the Co-Fe PBA-Prism, keeping the temperature for 1 to 2 hours and then stopping the heating, opening the reactor to cool down until the reactant is completely cooled to room temperature, taking out the reaction product from the reactor, and grinding it to obtain powdered CoFeO-Prism.

6. Use of a hollow prism-shaped cobalt iron oxide heterogeneous Fenton-like catalyst prepared by the method according to any one of claims 2 to 5, characterized in that: The CoFeO-Prism is used as a catalyst to activate peroxymonosulfate PMS, and is used to degrade refractory organic pollutants in organic wastewater.

7. The use according to claim 6, characterized in that: The organic pollutants include rhodamine B and tetracycline hydrochloride. When degrading organic wastewater, the mass ratio of the added amount of CoFeO-Prism to that of PMS is 1:0.15-6; the initial pH of the reaction is adjusted to 4-10; and the reaction temperature is 15-35°C.

8. The use according to claim 7, characterized in that: When degrading rhodamine in organic wastewater, the mass ratio of the added amount of CoFeO-Prism to PMS is 1:0.5; and the initial pH of the reaction is adjusted to 7-9.

9. The use according to claim 7, characterized in that: When tetracycline hydrochloride in organic wastewater is degraded, the mass ratio of the added amount of CoFeO-Prism to that of PMS is 1:1; and the initial pH of the reaction is adjusted to 8-10.